2013
DOI: 10.1111/pbr.12084
|View full text |Cite
|
Sign up to set email alerts
|

Selection for contrasting tocopherol content and profile in Ethiopian mustard

Abstract: Tocopherols are compounds present in oilseeds with major effect on nutritional and technological properties of seed oils. Brassica spp. mainly contain varying concentrations of a-tocopherol, with high vitamin E value, and c-tocopherol, which contributes to oil stability. The objective of this research was to select for contrasting tocopherol content and profile in Ethiopian mustard (Brassica carinata A. Braun). A collection of 211 F 4:5 lines was evaluated for tocopherol content and profile, and divergent sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In the present research, heritability was not estimated because the line with reduced γ -tocopherol content had been selected for this trait during several generations. It was selected from individual plants that exhibited the mutant trait within a germplasm accession with an average tocopherol profile close to the wild type [ 11 ]. The estimation of the minimum number of genes suggested that the trait is likely to be controlled by only two genes which, together with the absence of epistatic effects, may anticipate good response to selection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present research, heritability was not estimated because the line with reduced γ -tocopherol content had been selected for this trait during several generations. It was selected from individual plants that exhibited the mutant trait within a germplasm accession with an average tocopherol profile close to the wild type [ 11 ]. The estimation of the minimum number of genes suggested that the trait is likely to be controlled by only two genes which, together with the absence of epistatic effects, may anticipate good response to selection.…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopian mustard line BCT-6 is characterized by a reduced accumulation of γ -tocopherol, which results in an increased relative concentration of α -tocopherol and a reduced total tocopherol content [ 11 ]. The authors reported a tocopherol content of 127 mg kg −1 and α -/ γ -tocopherol ratio of 3.07 in BCT-6 compared to 185 mg kg −1 and α -/ γ -tocopherol ratio of 1.17 in the control line C-101.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations